Association of age to the linear and volumetric changes of maxillary permanent canine’s assessment through cone beam computed tomography: Across-sectional observational study - Hira Manan,; Sana Arbab,; Muhammad Izaz Ali,; Aiman Shaheryar,; Imran Khattak ,; Yusra Jamil Khattak, (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: To assess the impact of age on the pulp chamber-to-crown ratio of permanent maxillary canines using CBCT scans in participants from Peshawar’s dental teaching hospitals. Method: A cross-sectional study was conducted. The research was conducted at Khyber College of Dentistry and Sardar Begum Dental College in Peshawar, from September 2021 to June 2022. A total of 180 CBCT scans from participants aged 13 to 60 years, comprising 117 males and 63 females, were analyzed. The teeth were examined for crown length, width, volume, and pulp chamber dimensions. Measurements were taken in axial, coronal, and sagittal planes using Planmeca Romexis software. A significance level of p ≤ 0.05 was used for statistical analysis. Results: Participants were divided into five age groups. The highest frequency was in Group I (13-23 years, 41.1%), and the lowest in Group V (54+ years, 3.3%). The mean age was 27.23±10.48 years. Pearson correlation analysis showed a negative correlation between age and all measured variables, indicating a decrease in pulp chamber and crown sizes with increasing age. Significant differences were noted across age groups (p = 0.005). Conclusion: The study concluded that the size of the pulp chamber decreases as individuals age. Keywords: Cone-beam computed tomography, linear measurements, maxillary canine, Planmeca Romexis software